The Erv41–Erv46 complex serves as a retrograde receptor to retrieve escaped ER proteins - Shibuya, Aya (J Cell Biol, 2015)
Signal-dependent sorting of proteins in the early secretory pathway is required for dynamic retention of endoplasmic reticulum (ER) and Golgi components. In this study, we identify the Erv41–Erv46 complex as a new retrograde receptor for retrieval of non–HDEL-bearing ER resident proteins. In cells lacking Erv41–Erv46 function, the ER enzyme glucosidase I (Gls1) was mislocalized and degraded in the vacuole. Biochemical experiments demonstrated that the luminal domain of Gls1 bound to the Erv41–Erv46 complex in a pH-dependent manner. Moreover, in vivo disturbance of the pH gradient across membranes by bafilomycin A1 treatment caused Gls1 mislocalization. Whole cell proteomic analyses of deletion strains using stable isotope labeling by amino acids in culture identified other ER resident proteins that depended on the Erv41–Erv46 complex for efficient localization. Our results support a model in which pH-dependent receptor binding of specific cargo by the Erv41–Erv46 complex in Golgi compartments identifies escaped ER resident proteins for retrieval to the ER in coat protein complex I–formed transport carriers.